Motif Atlet Perempuan Menggunakan Hijab: - Annisa Adya Kencana; Oky Oxcygentri; Luluatu Nayiroh (Institut Agama Islam Nasional Laa Roiba Bogor, 2022)
There is a phenomenon that accurs in society, namely the use of identical hijabs used by Muslim Women an there are Muslim wpmen, although not so many of them are athletes. This research is motivated by the phenomenon where an athlete using the hijab is still considered to be difficult to get acceptance from his surroundings. In fact, there are still those who think that if an athlete uses the hijab, it is stil considered a layman and it will even make it difficult for them to get achievements. The purpose of this study was to determine the motives and communication experiences obtained by athletes wearing hijab at the Tengkorak Sport Community in Karawang City. This study uses a qualitative method with a Alferd Schutz Phenomenology. The results of the study were various motives obtained, namely because of religious law, the influence of the environment & support, as self-protection, and feeling calm. Positive experience such as support & appreciation, encouragement in oneself, accountability, self-confidence, and example. Negative experiences such as prejudice and intimidation. Keyword: Hijab, Athlete, Alferd Schutz Phenomenology